Home Base PSPS Dengan Pendekatan Arsitektur Postmodern - Gandhi Thaiba; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Home Base PSPS is the center of facilities owned by PSPS. Home Base PSPS consists of home stadium equipped with various facilities such as, Museum, Cafe, Restaurant, Retail Stores, Kiosk, VIP & VVIP Lounge, the Media Broadcast, and the Press Conference. PSPS Home Stadium is venues that held the match in Indonesia League system. Home Base PSPS design is done with Postmodern Architecture approach and apply the concept of